A comprehensive model for a sustainable maritimization: 3-Layer Holistic Maritimization Model. Issue 8 (16th November 2020) - Çetin, Oktay; Irak, Deniz Mehmet; Kahyaoğlu, Nurhan
ABSTRACT: Up to day, there is no consensus about the semantic explanations of the conceptions of maritime theory. In this study, we aimed to analyze the development process of sea related concepts, notions, and models; and to identify the maritime power elements as inputs and results as outputs by evaluating the evolving nature of the seas. We depicted the results of the study by a comparison chart and suggested a new input-output model namely "Three-layer Holistic Maritimization Model". In this model, we suggested a new notion called as "Maritimization" in the sense of a sustainable process to be planned and managed holistically with all layers. Maritimization process has key features such as maritime economics, maritime vision, sea power, maritime education and maritime culture. These elements can be accepted as parts of a puzzle. If one of the parts is ignored the system cannot work properly. In conclusion in the progress of decision process this model may offer an opportunity to understand the critical importance of maritimization process which may lead countries to some outputs such as wealth of nations, security of country and, innovational and libertarian thinking ability.